DNA sequencing reveal presence of the Lessepsian true limpet Cellana rota in the Syrian coasts of the Mediterranean - ALO, ALA’A; ALI AMMAR, IZDIHAR; KASHIRI, HADISE (Mediterranean Marine Science, 2025)
Many Red Sea species have entered the Eastern Mediterranean since the opening of the Suez Canal. Here, we report the presence of well-established populations of the Lessepsian true limpet Cellana rota (Gmelin, 1791) on the Syrian coasts of the Eastern Mediterranean. The collected specimens exhibited four different morphs and were 98.97-100% identical in Cytochrome Oxidase I (COI) sequence with C. rota. Six unique COI haplotypes, having 98.93 99.86% similarity, were noticed with variation at one to eight sites. The observed genetic divergence and dissimilarity were possibly low to assign four morphs to different species. In consistence with the phylogenetic data, our haplotype network exhibited that some alien individuals shared similar COI haplotype with those previously reported for indigenous populations from Eilat, Sinai and Hurghada, indicating the common origin from a single source in the Red Sea. In the present study, some implications of our findings for the systematics of Cellana species are also discussed. Based on our results, there is still some nomenclature and taxonomic confusion within Cellana species. Further multifaceted studies should be conducted to evaluate the taxonomy of this morphologically variable group. However, our data presented here could be a reliable reference for future investigations.